A Study on Online Gaming Addiction of the Middle School Student During the Pandemic - K., Aruna; SelvaKumar, Y. Stanley (Journal of Advanced Research in English & Education; Vol 8 No 2 (2023): Journal of Advanced Research in English & Education, 2023)
Hobby used to while away the time during the severe situation called pandemic, where people from all walks of life were made to sit at home. Few school kids, started using mobile for education purpose, later turned into addiction with influence from peer group. The category of students taken into consideration is of age group from 12 years to early 16 years, who are called middle school students. 50 questions were framed to bring out the likeliness of the gaming. To get the flavour with respect to the topic, data were collected from 300 samples who include both genders of class VI, VII & VIII. The group belongs to both urban and suburban students of Chennai, whose salary includes < 75,000 and > 75,000.